Rapid synthesis: Ensuring appropriate use of laboratory tests - Waddell, K; DeMaio, P; Bhuiya, AR; Alam, S; Wilson, MG (My University, 2023)
An in-depth synthesis of what is known based on the best available global research evidence (i.e., evidence syntheses) and local research evidence (i.e., single studies) and may include a scan of experiences from other countries and from Canadian provinces and territories, about appropriate use of laboratory tests in response to a decision-maker's request.
Keywords: use; laboratory; tests